Prevalence of, and Factors Associated with Hemodynamic Instability Among Women Presenting with Incomplete Abortion at a Tertiary Hospital in Southwestern Uganda - Kakama C; Agaba DC; Byamukama O; Kajabwangu R; Kengonzi E; Akol MA; Muhumuza A; Businge J; Turanzomwe S; Ainomugisha B; Kalyebara KP; Kayondo M; et al. (International Journal of Women's Health)
Caxton Kakama,1 David Collins Agaba,2 Onesmus Byamukama,3 Rogers Kajabwangu,1,3 Elizabeth Kengonzi,1 Mathiang Agany Akol,1 Amos Muhumuza,1 Julius Businge,1 Stuart Turanzomwe,1 Brenda Ainomugisha,1 Kato Paul Kalyebara,1 Musa Kayondo,1 Joseph Ngonzi,1 Wasswa George Muganwa,3 Henry Mark Lugobe1 1Department of Obstetrics and Gynecology, Mbarara University of Science and Technology, Faculty of Medicine, Mbarara, Uganda; 2Department of Physiology, Mbarara University of Science and Technology, Faculty of Medicine, Mbarara, Uganda; 3Department of Obstetrics and Gynecology, Mbarara Regional Referral Hospital, Mbarara, UgandaCorrespondence: Caxton Kakama, Department of Obstetrics and Gynaecology, Mbarara University of Science and Technology, Faculty of Medicine, Mbarara, 1410, Uganda, Tel +256 777465000, Email doncaxt@gmail.comBackground: Sub-Saharan Africa has a high abortion case-fatality rate, and most of these maternal deaths are due to hemodynamic instability which results from hemorrhage, especially in cases of incomplete abortion. Timely identification and management of hemodynamic instability is an important strategy for addressing the morbidity and mortality associated with incomplete abortion. This study, therefore, aimed at determining the prevalence and factors associated with hemodynamic instability among women presenting with incomplete abortion at Mbarara Regional Referral Hospital (MRRH).Methods: We conducted a cross-sectional study at the gynaecology ward of MRRH from January 2024 to April 2024. We consecutively enrolled women with incomplete abortion and collected data on socio-demographic, abortion- and medical-related factors, and measured their blood pressure and heart rate at admission. Obstetric shock index (OSI), the ratio of the heart rate to systolic blood pressure, was used as a measure of haemodynamic stability. A participant whose OSI was ≥ 0.9 was considered haemodynamically unstable. We performed a modified Poisson regression analysis to determine the factors associated with hemodynamic instability.Results: A total of 137 women with incomplete abortion were enrolled in this study with a mean age of 26.3 (± 5.93) years. The majority of the participants had first-trimester abortions (65.7%), were married (70.8%), and were from rural areas (60.0%). The prevalence of hemodynamic instability was 41.6% (95% CI: 33.6– 50.1). At multivariable regression analysis, gestation age ≥ 13 weeks (aPR 1.67, 95% CI: 1.12– 2.49) and post-abortion infection (aPR 1.75, 95% CI: 1.18– 2.60) were significantly associated with hemodynamic instability.Conclusion: Approximately two in every five women with incomplete abortion at MRRH were hemodynamically unstable at admission during the study period. Women with second trimester abortion and those with post-abortion infection are more likely to present with hemodynamic instability. We recommend strengthening routine assessment and management of hemodynamic instability among women with incomplete abortion.Keywords: incomplete abortion, hemodynamic instability, obstetric shock index, post-abortion infection